Ethnic and gender diversity in top level management and firm performance: Shareholder's perspectives - Hassan, R. (Bridgewater State College, 2017)
This study examines the relationship between demographic diversity in top management levels with a firms' financial performance using 84 non-financial companies in Malaysia. Demographic diversity consists of ethnic diversity and gender diversity. The top management level includes both the top management team and the board of directors. This study uses data from 2008 to 2012. Return on assets measures the financial performance. Ethnic and gender diversity measured by the number of Non-Malays and the number of females in top management respectively. This study incorporates descriptive statistics, correlation testing, and regression analysis. The results show that ethnic diversity in the top management team as well as in a board of directors has no impact on firm performance (ROE). However, the results of gender diversity have a positive impact on performance (ROE) in both perspectives (TMTs and BODs). © 2017 Journal of International Women's Studies.